Global research dynamics in the induced pluripotent stem cell and diabetes: A bibliometric analysis of the past twenty years - Jiatong Wang; Sirui Huang; Kaiyuan Li; Jing Li; Xin Huang (Regenerative Therapy, 2025)
Objectives: Induced pluripotent stem cells (iPSCs) have the potential to differentiate into insulin-producing β cells, offering a promising avenue for the treatment and research of diabetes. However, a comprehensive quantitative analysis of their specific impact in the field of diabetes has yet to be conducted. This study aims to analyze the current status and research hotspots of induced pluripotent stem cells in the field of diabetes over the past two decades, providing a reference for future research directions. Methods: This study performed a bibliometric analysis of recent literature on induced pluripotent stem cells in the field of diabetes, with data sourced from the Web of Science database. Using R software and VOSviewer, keyword clustering and research themes were analyzed to uncover trends and frontiers in this field. Results: The research included a total of 610 studies on induced pluripotent stem cells in the field of diabetes. In recent years, research in this field has shown a global upward trend, with the number of publications experiencing exponential growth from 2008 to 2021. However, the period from 2022 to 2025 is expected to be a plateau phase with fluctuations, gradually slowing down. The United States is the leading country in terms of publications, followed by China, Japan, the United Kingdom, and Italy. The United States not only leads in the number of publications but also has a broader network of international collaborators. Stem Cell Research and Diabetes are the most frequently published and cited journals. Currently, the application of iPSCs in studying the pathological mechanisms of diabetes and disease modeling has become a research hotspot. iPSCs provide an important in vitro platform for understanding the pathogenesis of diabetes and can also be used for drug screening, gene expression profiling, and studying the degeneration process of β-cells. Additionally, the use of iPSCs in the generation and regeneration of pancreatic β-cells, as a frontier of regenerative medicine and stem cell therapy, demonstrates the potential to restore normal islet function in diabetic patients. Furthermore, integrating immune evasion mechanisms and gene therapy, particularly by enhancing islet cell survival and function through immune regulation and genetic modification, is emerging as a new direction for diabetes treatment. Conclusion: The differentiation of induced pluripotent stem cells into β cells may offer a pathway to curing diabetes. This article systematically analyzes the current status and research hotspots of induced pluripotent stem cells in the diabetes field, providing valuable references for future clinical practice and research.